A spherical Si@silicon nitride ceramic powder and its preparation method and application

Through the preparation method of spherical Si@Si3N4 ceramic powder with core-shell structure, the problem of difficult spherical silicon nitride ceramic powder is solved, and the spherical ceramic powder with high thermal conductivity and high temperature stability is achieved, which is suitable for interface heat dissipation materials. It has low energy consumption and efficient preparation process.

CN117003562BActive Publication Date: 2024-12-17TSINGHUA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210466255.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-29
Publication Date
2024-12-17
Estimated Expiration
2042-04-29

AI Technical Summary

Technical Problem

Silicon nitride ceramic powder is difficult to spherical, which limits its application and development in the field of interface heat dissipation.

Method used

The preparation method of spherical Si@Si3N4 ceramic powder with core-shell structure is obtained by mixing silicon powder, silicon nitride diluent and reaction additives and performing combustion synthesis reactions to obtain spherical ceramics with silicon particle core and silicon nitride shell layer. The powder was then removed by sieving the silicon nitride particles with smaller particle sizes to obtain spherical Si@Si3N4 ceramic powder with an average particle size of 20-500 μm.

Benefits of technology

It has achieved a spherical Si@Si3N4 ceramic powder with high thermal conductivity, low impurity content, good crystallinity and uniform morphology. It is suitable as an inorganic thermal filler and semiconductor heat dissipation material, and has a high temperature stability and low energy consumption preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117003562B_ABST
    Figure CN117003562B_ABST
Patent Text Reader

Abstract

The invention discloses a spherical Si@Si 3 N 4 Ceramic powder and preparation method thereof. A ceramic powder with a core-shell structure of silicon nitride coated silicon is obtained by the method of the present invention. The powder monomer particles are spherical or nearly spherical in shape, the powder particle size is 2-500 μm, and it has the characteristics of high strength, not easy to be damaged, good silicon nitride coating effect on silicon, and high temperature oxidation resistance. The method comprises the following steps: after the silicon and silicon nitride reaction raw materials are uniformly mixed according to a proportion, the reaction raw materials are subjected to combustion synthesis, and the synthesized product is screened to obtain spherical Si@Si 3 N 4 Ceramic powder. Spherical Si@Si prepared by the present invention 3 N 4 In addition to the characteristics of traditional silicon nitride powder (high temperature resistance, high thermal conductivity, high strength, and wear resistance), ceramic powder also has the physical properties and spherical morphology of silicon. Through silicon nitride coating, it is beneficial to expand the application of silicon to the high temperature field and can be widely used in the field of powder preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ceramic preparation, and relates to a preparation technology of spherical Si@Si3N4 ceramic powder, and in particular to a preparation method of spherical ceramic powder of silicon nitride-coated silicon with a core-shell structure. Background Art

[0002] Silicon nitride ceramic powder has many excellent properties such as low density, high thermal conductivity, high hardness, good thermal stability and chemical stability. It is a type of material with the best comprehensive performance in the structural ceramic family. It is widely used in ceramic engines, cutting tools, thermal conductive substrates and other fields.

[0003] However, the difficulty in spheroidizing silicon nitride powder has limited its application and development in the field of interface heat dissipation. Summary of the invention

[0004] The purpose of the present invention is to provide a spherical Si@Si3N4 ceramic powder and a preparation method thereof.

[0005] The spherical Si@Si3N4 ceramic powder provided by the present invention has a core-shell structure, wherein the core of the core-shell structure is a silicon particle and the shell layer is a silicon nitride layer.

[0006] Furthermore, the average particle size of the spherical Si@Si3N4 ceramic powder is 20-500 μm, and the thickness of the shell layer is 5-50 μm.

[0007] The method for preparing spherical Si@Si3N4 ceramic powder provided by the present invention comprises the following steps:

[0008] (1) mixing silicon powder, silicon nitride diluent, and reaction additives uniformly and / or sieving to obtain a combustion synthesis raw material; in the combustion synthesis raw material, the mass percentage of the silicon powder is 30-95wt.%, the mass percentage of the silicon nitride diluent is 5-50wt.%, and the mass percentage of the reaction additive is 0-20wt.%;

[0009] (2) subjecting the combustion synthesis raw material to a combustion synthesis reaction to obtain a powder product.

[0010] The method further comprises the following step (3): screening the obtained powder product to remove silicon nitride particles with smaller particle sizes (generally removing particles with a particle size of less than 20 μm), and the remaining powder after screening is spherical Si@Si3N4 ceramic powder.

[0011] According to one embodiment of the present invention, in the method, for example, the purity of the silicon powder raw material in step (1) is >99wt.%.

[0012] According to one embodiment of the present invention, in the method, for example, the particle size range of the silicon powder in step (1) is 60-1000 mesh, specifically 60 mesh, 100 mesh, 200 mesh, 1000 mesh.

[0013] According to one embodiment of the present invention, in the method, for example, the silicon nitride diluent in step (1) is high-purity silicon nitride powder with an average particle size of 0.5-10 μm (specifically 2 μm, 4 μm), and the α-phase content of the high-purity silicon nitride powder is >60 wt.%.

[0014] According to one embodiment of the present invention, in the method, for example, the reaction additive in step (1) is one or more of ammonium chloride, ammonium fluoride, ammonium carbonate, ammonium bicarbonate, water, alcohol, silica sol, and silicon dioxide.

[0015] According to one embodiment of the present invention, in the method, for example, the mixing method in step (1) includes sand milling, ball milling, stirred milling, V-type mixer milling and / or drum milling.

[0016] According to one embodiment of the present invention, in the method, for example, the sieving in step (1) preferably includes sieving with a screen having 40-100 mesh openings; further preferably, the sieving in step (2) includes sieving with a screen having 60 mesh openings. The purpose of sieving is to improve the stacking state of the reaction raw materials, making the reaction raw materials more fluffy, which is conducive to subsequent combustion synthesis. It is preferable to select a screen with 40-100 mesh for sieving, and more preferably, a screen with 60 mesh openings can be selected. Too fine a screen may cause a change in the composition of the reaction raw materials; and too coarse a screen cannot fully improve the stacking state of the reaction raw materials.

[0017] According to one embodiment of the present invention, in the method, for example, in step (1), in the combustion synthesis raw material, the preferred mass percentage of the silicon powder is 50-90wt.%, the preferred mass percentage of the silicon nitride diluent is 5-45wt.%, and the preferred mass percentage of the reaction additive is 0-5wt.%.

[0018] According to one embodiment of the present invention, in the method, for example, in step (2), the reaction conditions of the combustion synthesis reaction are: in a nitrogen atmosphere, the pressure is 1-8MPa (specifically: 4MPa, 5MPa or 8MPa), the reaction temperature is >1500°C, and the reaction time is <2h.

[0019] Specifically, the combustion synthesis method is as follows:

[0020] The combustion synthesis raw materials obtained in step (1) are loosely packed in a reaction boat, and then the boat is placed in a combustion synthesis reaction device. After evacuation, high-purity nitrogen is filled in, and the pressure in the combustion synthesis reaction device is maintained at 1-8MPa. An igniter is ignited by an electrified tungsten wire coil or titanium powder is used as an ignition agent to induce a combustion synthesis reaction. After the reaction is completed, the pressure in the combustion synthesis reaction device begins to decrease, and the gas in the device is released at this time, and circulating water is passed for cooling; finally, an initial product (i.e., the powder product) is obtained; preferably, the purity of the high-purity nitrogen is above 99.9%.

[0021] According to one embodiment of the present invention, in the method, for example, the method of screening out silicon nitride in step (3) includes: screening method (screening the initial product, selecting a 60-200 mesh sieve according to the product particle size, and screening out silicon nitride products with smaller particle sizes), airflow screening method (screening out silicon nitride particles with smaller particle sizes by adjusting the amount of induced air), and physical sedimentation method (the initial product is precipitated in water, and products of different particle sizes can be obtained by controlling the sedimentation time).

[0022] The spherical Si@Si3N4 ceramic powder prepared by the above method also belongs to the protection scope of the present invention.

[0023] The average particle size of the spherical Si@Si3N4 ceramic powder is 20-500 μm (specifically 200 μm, 400 μm), and the impurity content (O, Fe, Al, Ca, Mg) is less than 1 wt.%. The metal impurities here are mainly introduced by Si raw materials, which are related to the crushing process of purchased commercial Si powder. O is introduced by oxidation.

[0024] The present invention also provides application of the spherical Si@Si3N4 ceramic powder.

[0025] The spherical Si@Si3N4 ceramic powder provided by the present invention can be used as an inorganic thermal conductive filler in thermal interface composite materials or semiconductor and chip heat dissipation materials.

[0026] The present invention has the characteristics of low energy consumption, simple equipment, energy saving, no pollution, no toxicity, etc. The prepared spherical Si@Si3N4 ceramic powder has the following outstanding advantages:

[0027] 1. Spherical Si@Si3N4 ceramic powder, the shell of a single particle is silicon nitride, the silicon nitride grains are tightly connected, and there is no amorphous glass phase remaining after the granulation method, so the thermal conductivity is higher. At the same time, its spherical morphology is conducive to the improvement of the powder stacking rate, which is very suitable for use as an inorganic thermal conductive filler in thermal interface composite materials.

[0028] 2. The spherical Si@Si3N4 ceramic powder obtained by the method has high thermal conductivity. Since the inside is made of silicon material, the thermal expansion coefficient of the powder is more compatible with silicon, and is more suitable for use in the semiconductor and chip heat dissipation fields.

[0029] 3. Since the silicon surface is coated with a dense layer of silicon nitride material, due to the high temperature resistance of silicon nitride material, the spherical Si@Si3N4 ceramic powder can be heated to 1414℃ in a nitrogen atmosphere without obvious weight loss. The silicon nitride on the silicon surface has a good protective effect on it. Ceramic powder with this Si@Si3N4 structure is beneficial to expand the application of silicon to the high temperature field.

[0030] 4. The spherical Si@Si3N4 ceramic powder obtained using the method has good crystallinity and uniform morphology.

[0031] 5. Save energy. Except for a small amount of energy required to initiate the reaction, the entire synthesis process is maintained and realized entirely by the heat released by the reaction, without the need for additional energy.

[0032] 6. High production efficiency and rapid synthesis reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings of the embodiments are briefly introduced below. Obviously, the drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.

[0034] Figure 1 is a SEM image of the silicon powder raw material used in Example 1;

[0035] Figure 2 is a SEM image of the silicon nitride diluent used in Example 1;

[0036] Figure 3 is the XRD analysis spectrum of the Si@Si3N4 product synthesized by combustion in Example 1;

[0037] Figure 4 is a SEM image of the combustion synthesized Si@Si3N4 product in Example 1;

[0038] Figure 5 The internal structure and element distribution diagram of the Si@Si3N4 product synthesized by combustion in Example 1;

[0039] Figure 6 is the XRD analysis spectrum of the Si@Si3N4 product synthesized by combustion in Example 2;

[0040] Figure 7 is the XRD analysis spectrum of the combustion synthesized Si@Si3N4 product in Example 3;

[0041] Figure 8 is the XRD analysis spectrum of the Si@Si3N4 product synthesized by combustion in Example 4;

[0042] Fig. 9 This is the SEM image of the combustion synthesized Si@Si3N4 product in Comparative Example 1. DETAILED DESCRIPTION

[0043] The spherical Si@Si3N4 ceramic powder of the present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope of protection of the present invention.

[0044] Unless otherwise indicated herein, all percentages are by mass.

[0045] For ease of understanding, the present invention is further explained below in conjunction with a specific example of preparing spherical Si@Si3N4 ceramic powder by combustion synthesis.

[0046] Example 1

[0047] Take the following components, 1000 mesh silicon powder (such as Figure 1 As shown), silicon nitride (average particle size 2 μm, as Figure 2 As shown), after mixing the above components with alcohol, using silicon nitride balls as the medium, ball milling on a rolling ball mill for 1h, and then vacuum drying at 80°C to obtain a combustion synthesis raw material (in the combustion synthesis raw material, the mass proportion of 1000 mesh silicon powder is 90wt.%, and silicon nitride (average particle size 2μm) is 10wt.%). The combustion synthesis raw material is then loosely packed in a reaction boat and placed in a combustion synthesis device. After vacuuming, 8MPa high-purity nitrogen is filled. Titanium powder is used as an ignition agent to induce a combustion synthesis reaction. After the combustion reaction is completed, the gas in the device is released, and when the circulating water is cooled to below 40°C, the chamber door is opened and the reaction product is taken out. The product is in a relatively soft block, gray as a whole, with a small amount of unreacted residual silicon powder on the surface. After cleaning, collecting, weighing and calculating the product, it can be seen that the product recovery rate is 95%. After the initial product is settled in water for 2min, the powder settled at the bottom is taken out, which is the spherical Si@Si3N4 ceramic powder.

[0048] The product was tested by XRD, and the test results were as follows: Figure 3 As shown, the analysis shows that the product is composed of silicon and silicon nitride, and the total amount of impurities is less than 1wt.%. Figure 3 The XRD pattern shown shows that the product has good crystallinity. Figure 4) It can be seen that the silicon nitride powder of this embodiment has good crystallinity, a spherical or nearly spherical morphology, and a particle size of about 200 μm. After cutting the particles, its internal structure can be observed, such as Figure 5 As shown, the single particle is dense as a whole, with no pores inside. The interior of the particle is silicon, and the surface is covered with a layer of dense silicon nitride material with a thickness of about 10μm.

[0049] The product was heated to above the melting point of silicon (1500°C) in a nitrogen atmosphere and kept warm for 8 hours. The powder was weighed after cooling, and the weight loss rate of the powder was <1%, indicating that the silicon nitride on the surface can well protect the internal silicon.

[0050] Example 2

[0051] Take the following components, 100 mesh silicon powder, silicon nitride (average particle size 4 μm), reaction additive ammonium chloride, mix the above components with alcohol, use silicon nitride balls as the medium, ball mill on a rolling ball mill for 1 hour, and then vacuum dry at 80°C to obtain a combustion synthesis raw material (in the combustion synthesis raw material, the mass proportion of 100 mesh silicon powder is 90wt.%, silicon nitride is 5wt.%, and the reaction additive is 5wt.%). Then, the combustion synthesis raw material is loosely packed in a reaction boat and placed in a combustion synthesis equipment. After vacuuming, fill with 8MPa high-purity nitrogen. Use titanium powder as an ignition agent to induce a combustion synthesis reaction. After the combustion reaction is completed, the gas in the device is released, and when the circulating water is cooled to below 40°C, the chamber door is opened and the reaction product is taken out. The product is in a relatively soft block, gray as a whole, with a small amount of unreacted residual silicon powder on the surface. After cleaning, collecting, weighing and calculating the product, it can be seen that the product recovery rate is 95%. The initial product is sieved (200 meshes), and the powder on the sieve is spherical Si@Si3N4 ceramic powder.

[0052] The powder product is composed of silicon and silicon nitride, with a total impurity content of less than 1wt.%, and good crystallization performance. The morphology is spherical or nearly spherical, with a particle size of about 400μm, and is also a core-shell structure of Si@Si3N4. The single particle is dense as a whole, with no holes inside. It can be seen that the inside of the particle is silicon, and the surface is covered with a layer of dense silicon nitride material.

[0053] The product was heated to 1000°C in air and kept warm for 8 hours. The powder was weighed after cooling. The weight loss rate of the powder was <1%, indicating that the silicon nitride on the surface protected the internal silicon very well.

[0054] Example 3

[0055] Take the following components, 200 mesh silicon powder, silicon nitride (average particle size 4 μm), reaction additive ammonium fluoride, mix the above components with alcohol, use silicon nitride balls as the medium, ball mill on a rolling ball mill for 1 hour, and then vacuum dry at 80°C to obtain a combustion synthesis raw material (in the combustion synthesis raw material, the mass proportion of 200 mesh silicon powder is 50wt.%, silicon nitride is 45wt.%, and the reaction additive is 5wt.%). Then, the combustion synthesis raw material is loosely packed in a reaction boat and placed in a combustion synthesis equipment. After vacuuming, fill with 5MPa high-purity nitrogen. Use titanium powder as an ignition agent to induce a combustion synthesis reaction. After the combustion reaction is completed, the gas in the device is released, and when the circulating water is cooled to below 40°C, the chamber door is opened and the reaction product is taken out. The product is in a relatively soft block, gray as a whole, with a small amount of unreacted residual silicon powder on the surface. After cleaning, collecting, weighing and calculating the product, it can be seen that the product recovery rate is 95%. The initial product is screened by air flow, and the spherical Si@Si3N4 ceramic powder is separated from the silicon nitride with smaller particle size by adjusting the amount of induced air. The powder product is composed of silicon and silicon nitride, with a total impurity content of less than 1wt.%, and the product has good crystallization performance. The morphology is spherical or nearly spherical, with a particle size of about 100μm. It is also the core-shell structure of Si@Si3N4. The single particle is dense as a whole, with no holes inside. It can be seen that the inside of the particle is silicon, and the surface is wrapped with a layer of dense silicon nitride material. The product is heated to 1000℃ in air and kept warm for 8h. After cooling, the powder weight is weighed. The weight loss rate of the powder is <1%, indicating that the silicon nitride on the surface protects the silicon inside very well.

[0056] Example 4

[0057] Take the following components, 60 mesh silicon powder, silicon nitride (average particle size 5 μm), reaction additive ammonium chloride, mix the above components with alcohol, use silicon nitride balls as the medium, ball mill on a rolling ball mill for 1 hour, and then vacuum dry at 80°C to obtain a combustion synthesis raw material (in the combustion synthesis raw material, the mass proportion of 60 mesh silicon powder is 50wt.%, silicon nitride is 45wt.%, and the reaction additive is 5wt.%). Then, the combustion synthesis raw material is loosely packed in a reaction boat and placed in a combustion synthesis equipment. After vacuuming, fill with 4MPa high-purity nitrogen. Use titanium powder as an ignition agent to induce a combustion synthesis reaction. After the combustion reaction is completed, the gas in the device is released, and when the circulating water is cooled to below 40°C, the chamber door is opened and the reaction product is taken out. The product is in a relatively soft block, gray as a whole, with a small amount of unreacted residual silicon powder on the surface. After cleaning, collecting, weighing and calculating the product, it can be seen that the product recovery rate is 95%. The initial product is screened by air flow, and the spherical Si@Si3N4 ceramic powder is separated from the silicon nitride with smaller particle size by adjusting the amount of induced air. The powder product is composed of silicon and silicon nitride, with a total impurity content of less than 1wt.%, and the product has good crystallization performance. The morphology is spherical or nearly spherical, with a particle size of about 100μm. It is also the core-shell structure of Si@Si3N4. The single particle is dense as a whole, with no holes inside. It can be seen that the inside of the particle is silicon, and the surface is wrapped with a layer of dense silicon nitride material. The product is heated to 1000℃ in air and kept warm for 8h. After cooling, the powder weight is weighed. The weight loss rate of the powder is <1%, indicating that the silicon nitride on the surface protects the silicon inside very well.

[0058] Comparative Example

[0059] Take the following components, 60 mesh silicon powder, silicon nitride (average particle size 5 μm), reaction additive ammonium chloride, mix the above components with alcohol, use silicon nitride balls as the medium, ball mill on a rolling ball mill for 1 hour, and then vacuum dry at 80°C to obtain a combustion synthesis raw material (in the combustion synthesis raw material, the mass proportion of 60 mesh silicon powder is 50wt.%, silicon nitride is 45wt.%, and the reaction additive is 5wt.%). Then, the combustion synthesis raw material is loosely packed in a reaction boat and placed in a combustion synthesis equipment. After vacuuming, fill with 0.5MPa high-purity nitrogen. Use titanium powder as an ignition agent to induce a combustion synthesis reaction. After the combustion reaction is completed, the gas in the device is released, and when the circulating water is cooled to below 40°C, the chamber door is opened and the reaction product is taken out. The product is in a relatively soft block, gray as a whole, with a small amount of unreacted residual silicon powder on the surface. After cleaning, collecting, weighing and calculating the product, it can be seen that the product recovery rate is 95%. The initial product is screened by airflow, and the spherical Si@Si3N4 ceramic powder is separated from the silicon nitride with smaller particle size by adjusting the amount of induced air. The powder product is composed of silicon and silicon nitride, and the total amount of impurities is less than 1wt.%, and the crystallization performance of the product is good. However, the product is a high-temperature fusion product of silicon nitride and silicon, and does not have a core-shell structure, and the morphology is not spherical (such as Fig. 9 shown).

Claims

1. A spherical Si@Si3N4 ceramic powder, which is a core-shell structure, wherein the core of the core-shell structure is a silicon particle and the shell layer is a silicon nitride layer; The preparation method of the spherical Si@Si3N4 ceramic powder comprises the following steps: (1) Silicon powder, silicon nitride diluent, and reaction additive are mixed uniformly and then sieved to obtain a combustion synthesis raw material; in the combustion synthesis raw material, the mass percentage of silicon powder is 30-95wt%, the mass percentage of silicon nitride diluent is 5-50wt%, and the mass percentage of reaction additive is 0-20wt%; (2) subjecting the combustion synthesis raw material to a combustion synthesis reaction to obtain a product containing spherical Si@Si3N4 ceramic powder; The method further comprises the following step (3): screening the product containing the spherical Si@Si3N4 ceramic powder to screen out the silicon nitride particles, and the powder remaining after screening is the spherical Si@Si3N4 ceramic powder; In the step (2), the reaction conditions of the combustion synthesis reaction are: reaction temperature>1500°C, reaction time<2h; In the step (2), the combustion synthesis method is as follows: the combustion synthesis raw materials obtained in step (1) are loosely packed in a reaction boat, and then the boat is placed in a combustion synthesis reaction device. After evacuation, high-purity nitrogen is filled in. The pressure in the combustion synthesis reaction device is maintained at 1-8MPa, and an ignition agent is ignited by an electrified tungsten wire ring or titanium powder is used as an ignition agent to induce a combustion synthesis reaction. After the reaction is completed, the pressure in the combustion synthesis reaction device begins to decrease, and the gas in the device is released at this time, and circulating water is used for cooling; finally, a product containing spherical Si@Si3N4 ceramic powder is obtained.

2. The spherical Si@Si3N4 ceramic powder according to claim 1, characterized in that: The average particle size of the spherical Si@Si3N4 ceramic powder is 20-500 μm, and the thickness of the shell layer is 5-50 μm.

3. The spherical Si@Si3N4 ceramic powder according to claim 1 or 2, characterized in that: In the step (1), the purity of the silicon powder raw material is >99wt%; the particle size range of the silicon powder is 60-1000 mesh; In the step (1), the silicon nitride diluent is high-purity silicon nitride powder with an average particle size of 0.5-10 μm, and the α-phase content of the high-purity silicon nitride powder is greater than 60wt%; In the step (1), the reaction additive is one or more of ammonium chloride, ammonium fluoride, ammonium carbonate, ammonium bicarbonate, silica sol, and silicon dioxide.

4. The spherical Si@Si3N4 ceramic powder according to claim 1 or 2, characterized in that: In the step (1), the mixing method includes one or more of sand milling, ball milling, stirred milling, V-type mixer milling, and drum milling; In the step (1), the screening includes screening using a screen with 40-100 mesh openings.

5. The spherical Si@Si3N4 ceramic powder according to claim 1 or 2, characterized in that: The purity of the high-purity nitrogen is above 99.9%.

6. The spherical Si@Si3N4 ceramic powder according to claim 1 or 2, characterized in that: The method for screening out silicon nitride includes: a screening method or a physical sedimentation method.

7. The spherical Si@Si3N4 ceramic powder according to any one of claims 1 to 6 is used as an inorganic thermal conductive filler in thermal interface composite materials or semiconductor and chip heat dissipation materials.